Fenomena Kesulitan Generasi Z dalam Mendapatkan Pekerjaan Ditinjau Perspektif Teori Kesenjangan Generasi - Fahmy Fotaleno; Denny Setiawan Batubara (Syntax Corporation Indonesia, 2024)
This study examines the phenomenon of difficulties faced by Generation Z in obtaining a job, using the perspective of generation gap theory. The purpose of this study is to understand the factors that cause this generation to experience challenges in the job market, as well as to analyze how the differences in values, skills, and expectations between Generation Z and previous generations contribute to these difficulties. Through a qualitative approach and secondary data analysis, the study found that a significant generation gap in terms of in-demand skills, career expectations, and adaptation to technological changes plays a major role in this issue. These findings are expected to provide insights for policymakers, companies, and educational institutions to develop more effective strategies in bridging the gap and increasing employment opportunities for Generation Z.